IMPLEMENTASI ALGORITMA FAST (FEATURES FROM ACCELERATED SEGMENT TEST) CORNER DETECTOR UNTUK PENGENALAN ALAT MUSIK TRADISIONAL KABUPATEN KUNINGAN BERBASIS AUGMENTED REALITY - Rio Priantama; Agus Wahyudin; Hendra Wibowo (FKOM UNIKU, 2021)
One of the cultures of Kuningan Regency that still exists today is traditional musical instruments whose numbers and types, historical information and how to play are increasingly rare to be introduced in schools and studios. One of the efforts to preserve and introduce traditional musical instruments in Kuningan Regency to the community, is by holding annual traditional musical instrument festivals, but these efforts have not been able to increase public knowledge about information from traditional musical instruments in Kuningan Regency. Technology that is able to provide information on traditional musical instruments and is able to be attractive and interactive is absolutely necessary as an alternative effort. Augmented Reality application by implementing the FAST Corner Detector algorithm can be built as an alternative to the introduction of traditional musical instruments in Kuningan Regency. This application was built using the RUP (Rational Unified Process) system development method. Application of Augmented Reality Introduction to Traditional Musical Instruments in Kuningan Regency can provide information about the types of musical instruments as well as examples of sounds and videos on how to play traditional musical instruments as a means of media in an effort to preserve traditional musical instruments in Kuningan regency in society, especially the younger generation.Keywords : Augmented Reality, FAST Corner Detector, Rational Unified Process,Traditional musical instrumen